2020
DOI: 10.3389/fnins.2020.00354
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Diagnostic Biomarkers for Motor Neuron Disease

Abstract: Motor neuron disease (MND) is a kind of neurodegenerative disease that selectively invades spinal cord anterior horn cells, brainstem motor neurons, cortical pyramidal cells and the pyramidal tract. The main clinical features are the symptoms and signs of impaired upper and lower motor neurons, manifested as muscle weakness, atrophy and pyramidal tract signs. Histopathology has shown the disappearance of pyramidal cells in the motor cortex, loss of motor neurons in the anterior horn of the spinal cord and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…As critical modulators of the brain and CNS transcriptome across neurodevelopment, aging and in neurological health and disease, both in human studies and in TgAD models, research evidence continues to implicate miRNAs as major epigenetic contributors to AD onset, incidence, neuropathology, epidemiology, disease course, severity and progression (Sethi and Lukiw, 2009;Lukiw, 2013a,b;Jaber et al, 2017Jaber et al, , 2019Wang et al, 2017;Condrat et al, 2020;Cole and Seabrook, 2020;Lukiw and Pogue, 2020;Moradifard et al, 2018;Wang and Zhang, 2020; 2020; Figure 3). Importantly, to date no single miRNA has been found that is diagnostic for the "prodromal" or "MCI" phase of AD or for any particular defined stage of the disease and this is likely to remain the case in future miRNA abundance studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As critical modulators of the brain and CNS transcriptome across neurodevelopment, aging and in neurological health and disease, both in human studies and in TgAD models, research evidence continues to implicate miRNAs as major epigenetic contributors to AD onset, incidence, neuropathology, epidemiology, disease course, severity and progression (Sethi and Lukiw, 2009;Lukiw, 2013a,b;Jaber et al, 2017Jaber et al, , 2019Wang et al, 2017;Condrat et al, 2020;Cole and Seabrook, 2020;Lukiw and Pogue, 2020;Moradifard et al, 2018;Wang and Zhang, 2020; 2020; Figure 3). Importantly, to date no single miRNA has been found that is diagnostic for the "prodromal" or "MCI" phase of AD or for any particular defined stage of the disease and this is likely to remain the case in future miRNA abundance studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent findings underscore the idea that it is very unlikely that any single miRNA in brain tissues, the ECF, CSF, blood serum, urine or any other biofluid compartments from multiple human populations will be predictive for AD at any stage of the disease. What might be particularly useful for significantly improved AD diagnostics, however, would be a selective, high-density panel of a "pathogenic and inflammatory neurodegeneration-associated miRNA family" that along with other molecular-based, gene expression-based or neuroimagingrelated biometrics could more accurately identify and predict the onset and course of AD-type change (Wang et al, 2017;Wang and Zhang, 2020;; see Figure 3). According to the systems biology approach, one of the pillars of precision medicine, a comprehensive evaluation, encompassing multiple pathophysiological mechanisms at different biological levels is needed to fully untangle the dynamics of AD and inform therapeutic decision-making at the individual level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations